2016
DOI: 10.1089/ten.tea.2015.0209
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Human Skin Equivalents on Porcine Acellular Peritoneum Extracellular Matrix forIn VitroIrritation Testing

Abstract: The irritancy of topical products has to be investigated to ensure the safety and compliance. Although several reconstructed human epidermal models have been adopted by the Organization for Economic Cooperation and Development (OECD) to replace in vivo animal irritation testing, these models are based on a single cell type and lack dermal components, which may be insufficient to reflect all of the components of irritation. In our study, we investigated the use of acellular porcine peritoneum extracellular matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Elevated IL-6 expression has also been detected in two-dimensional monolayers of cultured primary skin KCs, HaCaT cells, and dermal fibroblasts (Jung et al, 2016;Terunuma et al, 2001). Tsai et al (2016) detected elevated secretion of IL-6 using a full-thickness HSE constructed of HaCaT KCs in response to a number of skin irritants, and Schmalz et al (1998) observed similar findings when HSEs constructed of primary cells were incubated with metal-containing ceramics, whereas Bock et al (2018) found that IL-6 secretion was only increased when MUTZ-3 Langerhans-like cells were incorporated into their HSE on stimulation with irritants. IL-6 was also dramatically increased in a dermal fibroblast onlyepopulated three-dimensional model in response to cadmium chloride and lauryl sulfate (Augustin and Damour, 1995), suggesting that fibroblasts may be an important source of IL-6 in skin.…”
mentioning
confidence: 99%
“…Elevated IL-6 expression has also been detected in two-dimensional monolayers of cultured primary skin KCs, HaCaT cells, and dermal fibroblasts (Jung et al, 2016;Terunuma et al, 2001). Tsai et al (2016) detected elevated secretion of IL-6 using a full-thickness HSE constructed of HaCaT KCs in response to a number of skin irritants, and Schmalz et al (1998) observed similar findings when HSEs constructed of primary cells were incubated with metal-containing ceramics, whereas Bock et al (2018) found that IL-6 secretion was only increased when MUTZ-3 Langerhans-like cells were incorporated into their HSE on stimulation with irritants. IL-6 was also dramatically increased in a dermal fibroblast onlyepopulated three-dimensional model in response to cadmium chloride and lauryl sulfate (Augustin and Damour, 1995), suggesting that fibroblasts may be an important source of IL-6 in skin.…”
mentioning
confidence: 99%
“…To be more concrete, the degree of maturation of dermis is normally verified by the content of ECM secreted by the fibroblasts in dermis region. The stratified epidermis by differentiated keratinocytes is analyzed through an early differentiation marker of epidermis such as keratin 10 (K10) and late differentiation markers such as involucrin or filaggrin …”
Section: Resultsmentioning
confidence: 99%
“…Currently, gelatin hydrogels are widely used as bioink for their high biocompatibility . However, the printed construct's disadvantages of severe contraction, fast degradation, and limited lifespan cannot be ignored . Although the chemical cross‐linkers can improve such weakness, the cross‐linkers also have potential toxicities and damage …”
Section: Challenge and Outlookmentioning
confidence: 99%
“…5,9,10,44,45 However, the printed construct's disadvantages of severe contraction, fast degradation, and limited lifespan cannot be ignored. 16,46 Although the chemical cross-linkers can improve such weakness, the cross-linkers also have potential toxicities and damage. [47][48][49][50] Despite these obstacles, the developmental prospect of 3D bioprinting technology for skin regeneration is very optimistic.…”
Section: Challenge and Outlookmentioning
confidence: 99%